Cover Picture: Self‐Supported Polypyrrole/Polyvinylsulfate Films: Electrochemical Synthesis, Characterization, and Sensing Properties of Their Redox Reactions (ChemistryOpen 1/2017) - Otero, Toribio F. (ChemistryOpen, 2017)
The Front Cover picture shows an electrochemical cell featuring its most important parts (top) as well as three representative cyclic voltammetric responses (bottom), displaying the electrolyte potential window, the monomer oxidation–polymerization potential range, and the polymer oxidation–reduction potential window. More information can be found in the Full Paper by T. F. Otero and co‐workers on page 25 in Issue 1, 2017 (DOI: 10.1002/open.201600139).[Image: see text]